2021
DOI: 10.1111/cts.12980
|View full text |Cite
|
Sign up to set email alerts
|

Approval success rates of drug candidates based on target, action, modality, application, and their combinations

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 28 publications
1
44
0
Order By: Relevance
“…Phase I trials are typically performed after pre-clinical studies have suggested the potential utility of an investigational medication for a certain disease. However, <10% of medications entering phase I clinical testing will achieve FDA approval and reach the market ( 28 , 29 ). This has motivated the development of computational methods to reduce risk and increase efficiency of novel drug development.…”
Section: Discussionmentioning
confidence: 99%
“…Phase I trials are typically performed after pre-clinical studies have suggested the potential utility of an investigational medication for a certain disease. However, <10% of medications entering phase I clinical testing will achieve FDA approval and reach the market ( 28 , 29 ). This has motivated the development of computational methods to reduce risk and increase efficiency of novel drug development.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, studies using ML and quantitative modeling have been widely applied to clinical trials with varying goals and using diverse types of independent predictive variables. However, the annotation of clinical trial datasets is highly time-consuming and require domain expertise, due to which nearly all outcome prediction studies use commercially available, annotated clinical trial datasets (Lo et al, 2018, Feijoo et al, 2020, Zhavoronkov et al, 2020, Wong et al, 2019, Vergetis et al, 2020, Yamaguchi et al, 2021. A labyrinth set of studies evaluate various factors that affect trial outcomes and span a wide set of questions (see Feijoo et al, 2020 for a detailed review of ML and non-ML research).…”
Section: Machine Learning To Predict Clinical Trial Outcomesmentioning
confidence: 99%
“…A labyrinth set of studies evaluate various factors that affect trial outcomes and span a wide set of questions (see Feijoo et al, 2020 for a detailed review of ML and non-ML research). Yamaguchi et al (Yamaguchi et al, 2021), apart from implementing a logistic regression model that uses target, mechanism of action (MOA), modality, and application of drugs as features to predict clinical trial success, also provide a review that classifies literature based on the type of features used to predict clinical outcomes. We summarize the principal differentiation in Section 1.1.1 and refer the reader to the two recent studies (Feijoo et al, 2020, Yamaguchi et al, 2021 that provide exhaustive reviews of predictive algorithms.…”
Section: Machine Learning To Predict Clinical Trial Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In traditional drug discovery, the average period of new drug development pipelines takes at least 12 years from the initial discovery to the marketplace [ 23 ]. Although the pharmaceutical industry invested 83 billion USD worldwide on research and development (R&D) expenditures in 2019 [ 24 ], the success rate of a drug candidate starting from clinical trial to marketing approval was approximately 10~20%, which has not changed for the past few decades [ 25 ]. On the contrary, drug repurposing (also known as drug repositioning), which aims to identify new therapeutic uses of approved or investigational drugs, is a feasible and advantageous strategy with a lower development risk and time cost.…”
Section: Introductionmentioning
confidence: 99%